2017
DOI: 10.1037/pas0000402
|View full text |Cite
|
Sign up to set email alerts
|

Does reassessment of risk improve predictions? A framework and examination of the SAVRY and YLS/CMI.

Abstract: Although experts recommend regularly reassessing adolescents' risk for violence, it is unclear whether reassessment improves predictions. Thus, in this prospective study, the authors tested 3 hypotheses as to why reassessment might improve predictions, namely the shelf-life, dynamic change, and familiarity hypotheses. Research assistants (RAs) rated youth on the Structured Assessment of Violence Risk in Youth (SAVRY) and the Youth Level of Service/Case Management Inventory (YLS/CMI) every 3 months over a 1-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 81 publications
2
36
2
Order By: Relevance
“…This may be because this study used a long follow-up period (i.e., 8 years), during which time youth may have continued to show increases or decreases in risk. Another study found that, despite recommendations to regularly reassess risk, reassessing risk with the SAVRY and YLS/CMI did not improve risk predictions (Viljoen et al, 2016). Specifically, reassessments did not expire or show declines in predictive validity over a two-year follow-up period, nor did assessments improve as evaluators gained familiarity with youth via repeated reassessments.…”
Section: Sensitivity To Changementioning
confidence: 99%
See 1 more Smart Citation
“…This may be because this study used a long follow-up period (i.e., 8 years), during which time youth may have continued to show increases or decreases in risk. Another study found that, despite recommendations to regularly reassess risk, reassessing risk with the SAVRY and YLS/CMI did not improve risk predictions (Viljoen et al, 2016). Specifically, reassessments did not expire or show declines in predictive validity over a two-year follow-up period, nor did assessments improve as evaluators gained familiarity with youth via repeated reassessments.…”
Section: Sensitivity To Changementioning
confidence: 99%
“…This study was conducted as part of a larger study on risk assessment (Viljoen et al, 2016). Although that study also includes a 9-month reassessment, we focused on the baseline, 3-, 6-, and 12-month follow-ups, as researchers have recommended reassessments at these time points (Vincent et al, 2012;.…”
Section: Methodsmentioning
confidence: 99%
“…The youths with a prior arrest record scored higher in the risk domains than the reoffenders without a prior arrest record. The case of young repeat offenders who already had an arrest record represents a high-risk profile, or a profile of a criminal career [39]. Crimes committed by young people can be isolated incidents in their life, in this case, during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…As the ICU does not have a cut-off score to distinguish between adolescents scoring low and high on CU traits (Feilhauer et al, 2012;Ray, Frick, Thornton, Steinberg, & Cauffman, 2016), we used cut-off scores at the 25 th , 50 th , 75 th , 90 th , and 95 th percentiles (i.e., 19.50, 28.00, 32.00, 41.00, and 43.50, respectively). These percentiles have been used in similar analyses with self-report measures that include CU traits (i.e., APSD;Shaffer et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The present study used a prospective design. The ICU was completed by 70 adolescents as part of a larger longitudinal study examining mental health needs, risk, and strengths in adolescents on probation (e.g., Viljoen et al, 2016). Participants were recruited from 11 adolescent probation offices in the greater Vancouver area of British Columbia, Canada.…”
Section: Methodsmentioning
confidence: 99%